2011
DOI: 10.5039/agraria.v6i2a789
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de matéria seca e distribuição de nutrientes em duas cultivares de bananeiras irrigadas com água moderadamente salin

Abstract: Acúmulo de matéria seca e distribuição de nutrientes em duas cultivares de bananeiras irrigadas com água moderadamente salina RESUMO O acúmulo de matéria seca e a distribuição de nutrientes nas plantas são influenciados pelas interações competitivas existentes no ambiente e na cultura. O objetivo deste estudo foi avaliar o efeito do uso de água moderadamente salina no acúmulo de matéria seca e a distribuição de nutrientes em duas cultivares de bananeiras, Grand Naine e Prata Anão, na fase produtiva. O experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
2
Order By: Relevance
“…The reduction in Mg with increasing doses of biofertiliser is possibly related to the antagonistic effect of K and the toxic effect of Na present in the organic input. Soares et al (2011), working under field conditions, found results opposite to those of the present study, when irrigating plants of the banana cultivar Grand Naine with moderately saline water. These authors found the value for Mg as 27.69 g kg -1 .…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…The reduction in Mg with increasing doses of biofertiliser is possibly related to the antagonistic effect of K and the toxic effect of Na present in the organic input. Soares et al (2011), working under field conditions, found results opposite to those of the present study, when irrigating plants of the banana cultivar Grand Naine with moderately saline water. These authors found the value for Mg as 27.69 g kg -1 .…”
Section: Resultscontrasting
confidence: 56%
“…Contrary to that seen in the present study, Soares et al (2011), working under field conditions, found a leaf Ca content of 43.07 g kg -1 in the Grand Naine banana cultivar. Working with a crop of sweet pepper fertilised with pig biofertiliser, Sediyama et al (2014) found results similar to those in this study.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…In the present study, the average electrical conductivity of the wastewater was 1.128 dS m -1 (Table 2). Soares et al (2011) point out, however, that the banana tree may accumulate sodium in its rhizome to protect the other organs from sodium intoxication.…”
Section: Peelmentioning
confidence: 99%
“…Several studies have evaluated dry matter production and nutrient accumulation in banana organs, including bunches at just one time of the year, considering irrigated cultivation in the northeastern region of the country (SOARES et al, 2008;HOFFMANN et al, 2010a;HOFFMANN et al, 2010b;SOARES et al, 2011;DEUS et al, 2020a;DEUS et al, 2020b). However, this information can only be used in fertilization programs for places Oliveira et al (2022) Nutritional demand of 'Grande Naine' and 'Prata Comum' banana bunches in two growing seasons Rev Bras Frutic 2022; 44: n5: e-430 3 with water conditions similar to those found in these studies, thus limiting nutritional management in predominantly non-irrigated areas, a condition observed in one of the main bananas producing regions in Brazil, the Vale do Ribeira -SP.…”
Section: Introductionmentioning
confidence: 99%